THE IMPLEMENTATION OF FLIPPED CLASSROOM MODEL IN LEARNING DEGREES OF COMPARISON BY SENIOR HIGH SCHOOL STUDENTS - EMU, NERLAN KONGA; NALLEY, HILDA M.; HUAN, ELISNA (Academic Journal of Educational Sciences, 2022)
The aims of this research were to find out the students' ability in learning degrees of comparison by implementing the flipped classroom method. The tenth-grade students of SMA Kristen Pandhega Jaya, Indonesia were chosen as the subject of this research. The method used in this study is quantitative and qualitative methods and the research design was Classroom Action Research (CAR) in one cycle. The techniques of data collection were pre and post-test, observation sheets, focus group discussion, and field notes. The data were analyzed quantitatively and qualitatively. The results show that the students’ scores increased significantly from pre-test to post-test. In pre-test, only 3.33% student reached the Minimum Mastery Criteria, while in post-test it changed to 90%. Besides, the students’ mean score also improved from 30.4 to 81.4. This improvement happened because students pre-learned the materials, the learning it self was student-centered, and the flipped classroom was recycled. In summary, the flipped classroom model can improve the students’ ability in learning degrees of comparison.